Exome sequencing of sporadic childhood‐onset schizophrenia suggests the contribution of X‐linked genes in males - Ambalavanan, Amirthagowri; Chaumette, Boris; Zhou, Sirui; Xie, Pingxing; He, Qin; Spiegelman, Dan; Dionne‐Laporte, Alexandre; Bourassa, Cynthia V.; Therrien, Martine; Rochefort, Daniel; Xiong, Lan; Dion, Patrick A.; et al. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2019)
Childhood‐onset schizophrenia (COS) is a rare and severe form of schizophrenia, defined as having an onset before the age of 13. The male COS cases have a slightly younger age of onset than female cases. They also present with a higher rate of comorbid developmental disorders. These sex differences are not explained by the frequency of chromosomal abnormalities, and the contribution of other forms of genetic variations remains unestablished. Using a whole‐exome sequencing approach, we examined 12 COS trios where the unaffected parents had an affected male child. The sequencing data enabled us to test if the hemizygous variants, transmitted from the unaffected carrying mother, could mediate the phenotype (X‐linked recessive inheritance model). Our results revealed that affected children have a significantly greater number of X‐linked rare variants than their unaffected fathers. The variants identified in the male probands were mostly found in genes previously linked to other neuropsychiatric diseases like autism, intellectual disability, and epilepsy, including LUZP4, PCDH19, RPS6KA3, and OPHN1. The level of expression of the genes was assessed at different developmental periods in normal brain using the BrainSpan database. This approach revealed that some of them were expressed earlier in males than in females, consistent with the younger age of onset in male COS. In conclusion, this article suggests that X‐linked genes might play a role in the pathophysiology of COS. Candidate genes detailed here could explain the higher level of comorbidities and the earlier age of onset observed in a subset of the male COS cases.